1994
DOI: 10.2307/1243660
|View full text |Cite
|
Sign up to set email alerts
|

Retail‐Level Hedonics and the Valuation of Milk Components

Abstract: A retail‐level hedonic model for analyzing the value of milk components contained in aggregate dairy product commodities is developed and applied to household food consumption survey data. The findings support Perrin's conjecture that a hedonic approach applied at the retail level can be used to value milk components. Milk component values are found to be a function of household sociodemographic variables. The sample‐weighted average implicit fat value estimate was very similar to values published in two of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Market level data have come from a variety of sources, including auction records (McConnell and Strand, 2000;Vickner and Koch, 2001) and state purchasing agents (Morgan et al, 1979). Consumer level data have also come from a variety of sources, including supermarket scanner data, consumer surveys, and large, national databases such as the Nationwide Household Food Consumption Survey (Kawamura, 1999;Lenz et al, 1994;Shi and Price, 1998;Teisl et al, 2003;Maietta, 2003).…”
Section: Consumer Valuation Of Attributesmentioning
confidence: 99%
“…Market level data have come from a variety of sources, including auction records (McConnell and Strand, 2000;Vickner and Koch, 2001) and state purchasing agents (Morgan et al, 1979). Consumer level data have also come from a variety of sources, including supermarket scanner data, consumer surveys, and large, national databases such as the Nationwide Household Food Consumption Survey (Kawamura, 1999;Lenz et al, 1994;Shi and Price, 1998;Teisl et al, 2003;Maietta, 2003).…”
Section: Consumer Valuation Of Attributesmentioning
confidence: 99%
“…This is the approach taken when using hedonic pricing models, which consider the demand for a product or input as a function of its characteristics (Becker 1965;Lancaster 1966;Rosen 1974). Agricultural markets provide many opportunities to value commodities with nontradable attributes, and hedonic pricing approaches have been used to estimate the value of characteristics for a variety of agricultural products and inputs (e.g., Bowman and Ethridge 1992;Brorsen et al 1984;Espinosa and Goodwin 199 1;Jordan et al 1985;Lenz et al 1994;Tronstad et al 1992). Studies such as those by Kerr (1984) on beef and Walburger and Foster (1994) on hogs examine the demand for livestock sires using hedonic methods, modeling sire prices as functions of individual animal characteristics.…”
Section: A Hedonic Pricing Model For Evaluating the Genetic Merit Of mentioning
confidence: 99%
“…Under competition, Rosen (1974) has shown that these shadow prices reflect both marginal rate of substitution (on the demand side) and marginal rate of transformation (on the supply side) of the underlying characteristics. This has stimulated much research on the implicit pricing of characteristics imbedded in differentiated products (Jacobson and Walker, 1973;Lucas, 1975;Ball and Kirwan, 1977;Perrin, 1980;Updaw, 1980;Palmquist, 1984;Epple, 1987;St-Pierre and Scobie, 1987;Brorsen et al, 1998;Lenz et al, 1994;Gillmeister et al, 1996;Buccola and Iizuka, 1997;Combris et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…fat, protein). Previous research has investigated the pricing of dairy components at the farm level (Jacobson and Walker, 1973;Gillmeister et al, 1996;Buccola and Iizuka, 1997), at the retail level (Lenz et al, 1994), as well as the market level (Perrin, 1980;Schwart, 1985;St-Pierre and Scobie, 1987), all in a static framework. By considering dynamics, our analysis provides new insights on the implications of hedonic pricing.…”
Section: Introductionmentioning
confidence: 99%